-3(-3x-3)+3=66

Simple and best practice solution for -3(-3x-3)+3=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-3x-3)+3=66 equation:



-3(-3x-3)+3=66
We move all terms to the left:
-3(-3x-3)+3-(66)=0
We add all the numbers together, and all the variables
-3(-3x-3)-63=0
We multiply parentheses
9x+9-63=0
We add all the numbers together, and all the variables
9x-54=0
We move all terms containing x to the left, all other terms to the right
9x=54
x=54/9
x=6

See similar equations:

| 5x^2-51x+5=0 | | -66=3(5b-2) | | 5x+x+23=3x+34 | | 4,8/15,36=x/8 | | -z+1=1-z | | 64x^​2+64x+16=0 | | 64x​2​​+64x+16=0 | | x=0.02x^2+0.05x+0.04 | | 18=3y= | | 81z^2-4=0 | | 18-(3a-12)=8a | | -2(-2y+2)=16 | | -2(-2y=2)=16 | | 4x+33=-8x+9+5x | | 3a+7=12+4a | | 27x^2-72x-27=0 | | 15n/12=5 | | 1-x/14=10 | | 3(x-7)+5x=13+10x | | (1/4)-(5/6)=(1/a) | | (5+3)=4y | | v=1/3*3.14*16*6 | | 8x-8x+3x=0 | | 5(t-5)-3(2t-5)=25-8(3t+5) | | X3-12x=-96 | | 9x-25=11 | | 2x+3x+5+4x-14=360 | | 4x(x-5)=4x-5 | | 3(2y-1)=2(4y-5) | | 3(2y-1=2(4y-5) | | 6(2z-1)=7z+4 | | 2u+6=3+-3u+23 |

Equations solver categories